REFLEKSI UNTUK MODERASI ISLAM-INDONESIA - NANANG TAHQIQ (Jurnal Dialog, 2017)
This reflective article describes the author's experience of the common attitude of Indonesian Muslims who are basically uncourageous and afraid of murder, violence, terrorism, radicalism, or the like. Indonesian Muslims prefer to moderate attitude than extreme one. Therefore, Indonesian Muslims--both individual and communal-- will always be moderate from the first onwards. Both experiences while living abroad (Canada) and notably in the country (Indonesia) proved to the author that Indonesian Muslims did not like violence. Moreover, the evidences suggested that the source of violence is external influence. One of related experiences on how Indonesian Muslims abroad tend to avoid violence was also experienced by the author during his lecture at McGill University, Montreal, Canada. In this article the author sketches briefly his story and conclude that the basic characteristics of Indonesian Muslims is moderate, and moderate Muslim trends or movements will be well acceptable and grow up.